SIADH Induced by Pharyngeal Squamous Cell Carcinoma: Case Report and Literature Review. (22nd August 2016) - Arshad, Hafiz Muhammad Sharjeel; Rodriguez, Aleida; Suhail, Faten
Abstract : Background . The Syndrome of Inappropriate Antidiuretic Hormone (SIADH) is considered to be the most common cause of euvolemic hyponatremia. The most common malignancy associated with SIADH is small cell lung cancer. We present a rare case of a patient with SIADH secondary to well differentiated squamous cell carcinoma of the naso-oropharynx. Case . A 46-year-old Caucasian woman presented to emergency department with four-week history of progressive dysphagia. On examination, she was found to have a pharyngeal mass. CT scan and MRI of neck confirmed a mass highly suspicious of carcinoma. Patient's serum sodium level decreased to 118 mEq/L and other labs including serum and urine osmolality confirmed SIADH. She was started on fluid restriction and oral sodium tablets which gradually improved her serum sodium levels. Biopsy confirmed diagnosis of squamous cell carcinoma of pharynx. Conclusion . SIADH can be caused by squamous cell carcinoma. Appropriate management includes fluid restriction.